NAVIGATING AFFECTIVE COMMITMENT AND TURNOVER INTENTION: THE MEDIATING ROLE OF JOB SATISFACTION IN CHARISMATIC LEADERSHIP EFFECTS WITHIN PAKISTAN'S PHARMACEUTICAL INDUSTRY (Contemporary Journal of Social Science Review, 2025)
The effects of charismatic leadership on employee’s attitudinal outcomes including affective commitment, turnover intention, and job satisfaction are the main subjects of the current study, set in the context of the pharmaceutical industry in Pakistan with a particular focus on job satisfaction as a mediator in this relationship. Using a quantitative research approach, this study used convenience sampling method to survey the respondents whereby questionnaires were administered on the employees in 28 pharmaceutical firms in Lahore, Pakistan. To test the association among charismatic leadership, affective commitment, turnover intention, and job satisfaction, the survey was followed up and 210 questionnaires completed in all respect were analyzed using statistical methods like correlation and mediation. The results demonstrated that charismatic leadership, which is based on characteristics like vision and enthusiasm as well as emotional intelligence, significantly influences job satisfaction. Because of this, it has an effect on increased affective commitment and decreased expectation of the workforces to leave the organization. The findings also emphasize on the significance of job satisfaction as a mediator in the said relationship aiming to assist organizations to enhance charismatic leadership, which consequently improves employee retention and engagement. The study’s recommendations include that the organizations to focus on their leadership development programmes and create a conducive workplace environment, which lead to enhanced degree of workers’ job satisfaction, loyalty and commitment towards the organization.